KEHIDUPAN EKONOMI DRIVER GOJEK DI KOTA JAMBI 2017 – 2022 - Suseno, Iwen; Heidi Karmela, Siti; Yanto, Ferry (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2024)
The purpose of this study is to find out about the existence of gojek drivers in fulfilling the needs of life and their role in the online transportation service sector in Jambi City 2017 – 2022. The research method used is the historical method which consists of four stages, namely source collection (heuristic), criticism and source selection, interpretation, and writing (historiography). The findings show that Gojek drivers are one of the jobs that can be the livelihood of the Jambi people. Gojek services can help motorcycle taxis who can use their time as effectively as possible in carrying out their profession as ojek drivers who are not too difficult to find customers, and also make it easier for people to travel, with various traffic jams in big cities. Gojek is an Indonesian app with transportation services, food delivery, bill payment, and even health services.